PENGARUH LATIHAN VARIASI TERHADAP KETERAMPILAN PASSING BAWAH BOLA VOLI PADA TIM BOLA VOLI JUNIOR PUTRA PONOROGO KOTA KISARAN PROVINSI SUMATERA UTARA - Fauzi Astaman; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The aim of this research was to find out the Influence of Variation Exercises Toward Passing Down Volleyball Skill on Men Junior Volleyball Team Ponorogo Kisaran City North Sumatra. This research was experimental research and using one group pree test - post test design. The population of this research was the men junior volleyball team Ponorogo which consist of 9 people. While, the sample was total sampling, which all population become the sample (Sugiyono, 2010:96). The instrument was passing down volleyball skill test. Then, the data was analyzed by using the statistic. The normality of data was analyzed b using liliefors in significant value α (0.05). The hypothesis was there is a significant Influence of Variation Exercises Toward Passing Down Volleyball Skill Men on Men Junior Volleyball Team Ponorogo Kisaran City North Sumatra. Based on the result, the mean score of pree test was 10,00 and post test was 14,80 the enhancement of the mean score was 4,80 with t test that tcount = 18,769 > ttable = 1,860. It means that tcount > ttable. It could be conclude that there is a significant Influence of Variation Exercises Toward Passing Down Volleyball Skill on Men Junior Volleyball Team Ponorogo Kisaran City North Sumatra.Keyword: Variation Exercises, Passing Down Volleyball Skill